2013
DOI: 10.1645/ge-2949.1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and In Vitro Culture of Trypanosomes FromLeptodactylus ocellatusFrom the Atlantic Forest in a New Experimental Culture Medium

Abstract: The purpose of this study was to verify the in vitro development of Trypanosoma sp. isolated from Leptodactylus ocellatus frogs under a new protocol using a biphasic medium composed of Novy, McNeal, and Nicolle (NNN) blood agar medium as a solid phase and liver infusion, brain heart infusion, and tryptose (LIBHIT) medium as a liquid phase. Blood forms, collected by cardiac puncture or after the maceration of different organs, were inoculated in culture tubes containing the biphasic medium composed by NNN and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Blood and axenic trypanosome cultures were fixed in 2.5 % glutaraldehyde in 0.1- M cacodylate buffer (pH 7.2) containing 5 mM calcium chloride and 3.7 % sucrose. For SEM, cells were washed and adhered to glass coverslips previously coated with 0.1 % of poly- l -lysine and processed (dehydrated, critical point dried and coated), according Lemos et al [ 51 ]. Leeches were sectioned in the longitudinal and transverse directions, fixed and critical point dried for SEM (as described above), adhered to glass coverslips using adhesive tape, and coated with a 20-nm-thick gold layer, using a Bal-Tec CPD030 sputtering device.…”
Section: Methodsmentioning
confidence: 99%
“…Blood and axenic trypanosome cultures were fixed in 2.5 % glutaraldehyde in 0.1- M cacodylate buffer (pH 7.2) containing 5 mM calcium chloride and 3.7 % sucrose. For SEM, cells were washed and adhered to glass coverslips previously coated with 0.1 % of poly- l -lysine and processed (dehydrated, critical point dried and coated), according Lemos et al [ 51 ]. Leeches were sectioned in the longitudinal and transverse directions, fixed and critical point dried for SEM (as described above), adhered to glass coverslips using adhesive tape, and coated with a 20-nm-thick gold layer, using a Bal-Tec CPD030 sputtering device.…”
Section: Methodsmentioning
confidence: 99%
“…LIT medium was made according to the ATCC 1029 medium recipe with modifications: liver broth (Oxoid, 9 g L −1 ), lab-lemco powder (Oxoid, 5 g L −1 ), NaCl (5 g L −1 ), Na 2 HPO 4 (7 g L −1 ), glucose (1 g L −1 ) were added to DDW and sterilized by autoclaving. Ten percent heat-inactivated horse serum, Pen/Strep and laked horse blood (20 mL L −1 ) were added as a source of haemin (Lemos et al ., 2013). Laked horse blood was prepared by adding an equal volume of DDW to horse blood (Serum Australis) and freeze/thawing it three times at 56°C.…”
Section: Methodsmentioning
confidence: 99%
“…Brazil harbor the highest anuran diversity of the world with more than 1000 species (Segalla et al, 2016) and the studies of anuran trypanosomes reported in Brazil include the description of few species infecting hosts from different families: Trypanosoma borreli Marchoux & Salimbeni, 1907from hylids, Trypanosoma leptodactyli Carini, 1907and Trypanosoma herthameyeri Attias et al, 2016 leptodactylids (Carini, 1907;Marchoux & Salimbeni, 1907;Attias, et al, 2016). Phylogenetical studies revealed great diversity of Brazilian anuran trypanosomes reflecting remarkable morphological variation of bloodstream trypomastigotes, and ultrastructural differences of in vitro developmental stages (Ferreira et al, 2007;Leal et al, 2009;Lemos et al, 2008;2013;Ferreira et al, 2015;Attias et al, 2016). The objective of this study was to characterize anuran trypanosomes in naturally infected hosts from the Brazilian Midwest, including the transition areas between Cerrado and Rain Forest.…”
Section: Introductionmentioning
confidence: 99%